(untitled) - D C Green (London, 1993)
The book provides a comprehensive coverage the more important circuits and techniques used in modern digital electronic circuitry. The various logic families are discussed and their relative merits considered but the description of the digital circuits, such as counters, is illustrated by reference to the two most popular families, i.e. TTL and CMOS, only
Keywords: electronic engineering,electronics